UiTM News Hub: Arau International Poetry Festival 2021: a creative outlet for expressing hope and resilience / Dr Razlina Razali and Dr Latisha Asmaak Shafie - Razali, Razlina , Dr; Shafie, Latisha Asmaak, Dr (2021)
ARAU, 6 November 2021 - 112 local and international poets and poetry enthusiasts gathered virtuallyon Saturday for the Arau International Poetry Festival 2021 (AIPF 21). The event, which was anextension of last year's Arau Poetry Festival 2020 was organised by Academy of Language Studies, UiTM Perlis Branch and Research Interest Group (RIG) Digital Communicators in collaboration with RIG Suara Kreatif Madani (SuKMa), Academy of Contemporary Islamic Studies and Innovation and Expertise Management Unit (InExMa), Division of Research, Industry, Community, Alumni, Entrepreneurship and Network (RICAEN), UiTM Perlis Branch.